Design Tool Typeversatile Perajang Blade Sliding By Using The Principles Of Steinermechanical RALPH - Danuri R; May Amaliawati (International Conference on Engineering and Technology Development (ICETD), 2017)
Chips is a kind of snack in the form of thin slices of tubers, fruits, or vegetables, ,Chips belonging to types of food crackers, foods that are dry and crisp with a high fat content.Cassava chopper machine design concept refers to the design concept Darmawanie with several stages, among other needs, the project definition, project and preparation of the technical specifications of the product, product concept design, product design, to document for the manufacture of the product. The next process is to analyze the needs, taking into consideration planning, and pay attention to the demands planning.Chopper machine tuber is a tool to chop the bulbs into thin sheets with a thickness of 1 s / d 2 mm. Not only that, this machine can also produce stick-shaped incision because blades can be changed as needed. PERAJANG tool versatile type of blade sliding by using the principle of mechanical ralph steiner, which is a principle of abstraction based on gear and engine, and this is the latest tool that does not exist, the working principle of this machine is almost identical to the working principle of the crankshaft is to move back and forth from crank shaft.Dengan blade on the right and left, can multiply the number of pieces results from the number of blades and the hopper can be expanded in number